Importance of miR-125a-5p and miR-122-5p expression in patients with HBV infection - Lak, Ramin; Yaghobi, Ramin; Garshasbi, Masood (Cellular and Molecular Biology, 2020)
MicroRNAs (miRNAs) as a small RNA and post-transcriptional modulator are shown to have regulatory effects for different cellular activities and pathways, such as metabolism, virus replication and also cell growth. In addition, miRNAs can regulate the replication of the hepatitis B virus (HBV). Therefore, the expression profile of miRNAs was evaluated in HBV infected patient groups and healthy controls. The expression levels of following microRNAs (as noninvasive biomarkers) were compared in two experimental (those with various stages of HBV infection) and control groups to evaluate their diagnosis ability: miR-122-5p, miR-125a-5p, miR-199a-3p, miR-210-5p, miR-205-5p, miR-155-5p, miR-372-5p, and miR-1-5p. RNA extraction was performed for 45 serum samples. The miRCURY LNAâ„¢ Universal RT-miRNA-PCR system and miRNA PCR panels were used for measuring microRNA expression profiles. To normalize quantitative values, the endogenous reference by UniSp6 expression was used.Serum miR-125a-5p and miR-122-5p were significantly higher in patients in different stages of HBV infection (p<0.001) than in controls (p<0.001). Receiver operating characteristic (ROC) curve analyses suggested that serum miR-125a-5p and miR-122-5p have significant diagnostic value for HBV infection. A significant difference was not found in terms of serum levels of other miRs (miR-199a-3p, miR-210-5p, miR-205-5p, miR-155-5p, miR-372-5p and miR-1-5p). Results suggest that miR-125a-5p and miR-122-5p can be used as possible noninvasive biomarkers for monitoring of HBV infection need to confirm in future completed studies.